Acceptability and perceived impact of the IMAGINE intervention - White, Erica Christine (My University, 2022)
Introduction: Perinatal depression is common, and risk among young parents is elevated. Phone-based Cognitive Behavioral Therapy (CBT) can be one way of offering more accessible mental health care to young parents.Objective: We examined the acceptability and perceived mental health impacts of a digital adaptation of an evidence-based CBT intervention (IMAGINE) based on 9 in-depth interviews (IDIs) with intervention recipients. Method: IDIs were analyzed using a mixture of inductive coding driven by themes emerging from the transcripts and deductive coding based on themes from the interview guide. Transcripts were coded using Dedoose software. My analysis focused on perceived acceptability and mental health impact of the IMAGINE pilot as well as recommendations for future programming. Results: In this qualitative study of interviews with participants exiting the IMAGINE study, we found that several aspects of IMAGE were viewed as helpful. In particular, participants highlighted one-to-one support from the facilitator, connection with other parents, and regular opportunities to reflect on their mood through digital surveys. Several participants reported that IMAGINE increased their openness to mental healthcare in the future, and several noted a better ability to regulate their emotions. Participants appreciated the intervention’s flexibility and were appreciative of the changes that were made to message frequency and pace during the pilot itself. Introversion, technology access barriers, and limited time were all barriers to participation; facilitators to participation included social support and information gained from the intervention. Participants offered several points of important feedback to consider in future iterations. First, they would like changes to the frequency or timing of the synchronous weekly Zoom calls with the facilitator and other participants, noting that having more flexible scheduling options would be helpful, including the ability to have multiple options for Zoom times per week. Several participants recommended having more onboarding at the beginning of the pilot, both to gain clarity about the intervention and also to help learn the technology. Although the program was designed to be implemented virtually, common feedback was that participants would have preferred having at least one or a few in-person meetings throughout the program. Since the sample size was small, low engagement from other program members was a common barrier for further engagement. Conclusion: The IMAGINE intervention may be useful for offering flexible and accessible CBT in a way that is responsive to the needs of young birthing parents, who are at high risk of perinatal depression. It is paramount that end-user feedback is considered, as programs designed to meet the needs of young parents should be centered around their experiences. Further research is needed to evaluate the IMAGINE program’s clinical effectiveness, and further interventions can make improvements based on participant feedback from this research. Young parents deserve to feel safe and supported during pregnancy and postpartum, and to have access to services that can help them thrive. Keywords: perinatal depression, adolescent parent, mental health access
Thesis (Master's)--University of Washington, 2021
Keywords: adolescent parent; mental health; mHealth; perinatal depression; Mental health; Global Health